TEACHER'S QUESTIONING STRATEGY IN TEACHING PROCEDURE TEXT FOR THE TENTH GRADE AT SMAS PRIMBANA MEDAN - Putri Syahrani Achsyur Nasution; Nora Ronita Dewi (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
The aims of this research are to investigate the questioning strategy that teacher used and how the teacher applied the questioning strategy in teaching procedure text for the tenth grade at SMAS Primbana Medan.  Qualitative descriptive method is the method used in this research to achieve the research objectives.  The data were taken by observed the teaching learning process procedure text, interviewed the English teacher, and video recording in order to find out questioning strategy that the teacher used and how the application of the questioning strategy.  In the learning process of teaching and learning, teacher actively use question, the research outcomes   shown   that the teacher use Questioning Planning Strategy 12 times (26%) and Questioning Controlling Strategy 34 times (74%).   The teacher applied Questioning controlling strategy when asking individual students. Meanwhile, when asking the whole class or group of students, teachers use a combination of Questioning Controlling and Questioning Planning strategies.